Digital Literacy Skills and System Quality as Predictors of Learning Management Systems Use of Postgraduate Students in Ibadan Nigeria - Adegbore, Adebayo Muritala; Tella, Adeyinka; Jide, Ayoola (IJIE (Indonesian Journal of Informatics Education), 2023)
The use of learning management systems (LMS) was observed to be weak among students in Nigeria. Therefore, digital literacy skills and system quality were used as predictors to predict LMS use among postgraduate students in universities in Ibadan, Nigeria.  A survey design of the correlational type was adopted. At the same time, the population of the study comprised all the 4,750 postgraduate students of two universities in Ibadan, Nigeria, and 328 postgraduate students were drawn using a multi-stage sampling technique. The instrument adopted for data collection was a questionnaire which had three sections. The questionnaire return rate was 316 copies, representing a 96.3% retrieval rate. Pearson’s Product Moment Correlation Coefficient and multiple regression analysis were conducted to test the null hypotheses at a 0.05 significance level. A significant relationship between digital literacy skills and the use of learning management (r =.319; p < 0.05) was found, while a significant relationship between system quality and the use of learning management systems (r =.501; p < 0.05) was equally established. There is a significant relationship between digital literacy skills and LMS system quality (r =.529; p < 0.05). Furthermore, a joint influence of digital literacy skills and system quality on the use of learning management systems of postgraduate students in universities in Ibadan, Nigeria (F =53.594; R=0.505; p < 0.05) was established. It was recommended that university management and lecturers should ensure the system quality of the LMS type to be adopted must support the convenience of use and have fewer technicalities in its use.